Langage égalitaire : vers une rationalisation des procédés et des approches - Éliane Viennot (Cahiers d’histoire.)
Inclusive writing, a major subject of controversy in recent years, “mortal peril” for some people, is a matter of historical and social issues spanning centuries. Based on a history of language and women, historian Éliane Viennot studied the process of masculinization of the French language with the institution of the French Academy in the 19th century. Language is not immutable, it is built socially according to codes and over the centuries, it participates in the invisibility of women through a well-known creed: "the masculine prevails over the feminine." It proposes common recommendations for an egalitarian language that integrates women and men. From the middle point and the agreements to the feminization of the names of trades, these uses question the representations of gender in our societies through the written word.